Massa Dan Fungsi Ventrikel Kiri Pada Malnutrisi Energi Protein Tipe Marasmus - Herlina Dimiati; Sudigdo Sastroasmoro; Sukman Tulus Putra; Aryono Hendarto (Jurnal Kardiologi Indonesia, 2011)
Objectives. To determine the left ventricular mass, the left ventricular systolic anddiastolic function of children suffering protein energy malnutrion marasmic type. Material.Pediatric patients suffering protein energy malnutrion marasmic type who came for treatment in Division of Pediatric Metabolic Nutrition, Departement of Child Health, Medical Faculty, Cipto Mangunkusumo Hospital Jakarta between June to August 2007.Methods. A cross-sectional study was conducted to evaluate left ventricular systolic function (EF and FS), left ventricular diastolic function (E, A, ratio E/A and IVRT) and left ventricular mass (LVDDi, LVDSi, LVMi) by Ultrasonography Sonos 4500. The student t-test was used, statistical significant was assumed with a< 0.05 with program SPSS 15.0 version. Results. Out of 25 subjects examined (9 male and 16 female), the left ventricular mass in marasmic patients was lower compared to control. Mean of LVMi (g/m2) marasmic and control each 22.5 (SD 17.7) and 39.1 (SD 41.1); p < 0.02. Systolic and diastolic function in marasmic were lower than the control and the difference was statistically significant. Mean EF in marasmic and control each 56.4% (SD 7.2) and 73.2% (SD 7,7) ; p = 0.001. Mean FS 28.6% (SD 4,9) and 40.4% (SD 8.7) ; p = 0.001. Mean ratio E/A in marasmic and control each 1.79 (SD 0.5) and 1.54 (SD 0.2); p = 0.04Conclusions. The left ventricular mass in marasmic was lower than a child with good nutrition. The left ventricular systolic and diastolic function of marasmic patients were disturbed. The left ventricular diastolic function seen in restrictive pattern.